Job creation and improved consumer health through commercialisation of tiger nut yoghurt: a willingness to pay analysis - Wongnaa, C. A. (Springer Open, 2021)
This article is published in Springer Open and also available at https://doi.org/10.1186/s40497-018-0139-x